2002
DOI: 10.1038/ncb872
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB2 p100 is a pro-apoptotic protein with anti-oncogenic function

Abstract: Nuclear factor-kappa B (NF-kappa B) promotes cell survival by upregulating expression of anti-apoptotic genes, a process that is antagonized by inhibitors of kappa B (I kappa B) factors. The only NF-kappa B family member known to be mutated in human cancer is NF-kappa B2 p100 (ref. 2), a factor with I kappa B activity. Here, we report the isolation from irradiated mouse tumour cells of a complex that induces caspase-8 activity in cell-free assays and identify p100 as an essential component of this complex. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…It has been reported that the p100 protein can have a p53-dependent proapoptotic function (Wang et al, 2002). However, this is not likely to be the case in our study for several reasons.…”
Section: Relb Enhances Radiation Resistance S Josson Et Almentioning
confidence: 56%
“…It has been reported that the p100 protein can have a p53-dependent proapoptotic function (Wang et al, 2002). However, this is not likely to be the case in our study for several reasons.…”
Section: Relb Enhances Radiation Resistance S Josson Et Almentioning
confidence: 56%
“…13 It was, however, also suggested that NFkB2 (p100) might be a direct activator of programmed cell death. 14,15 NFkB was shown to be involved in acute pancreatitis. 16 Activation of NFkB was detected as early as 10 min after supramaximal stimulation in the cerulein model of acute pancreatitis and seemed to limit the damage induced, while blocking NFkB activation had an adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…In short, these p100 truncations may promote the activity of the non-canonical p52-RELB NF-kB pathway. However, the C-terminal truncations in p100 also remove a caspase-8 recruitment 'death domain' (Wang et al, 2002), suggesting that these p100 truncations could also contribute to oncogeneis by rendering cells more resistant to apoptotic stimuli.…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%